2019
DOI: 10.1177/0276236619869163
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Interactions and Inner Speech

Abstract: Similarities and differences between inner speech and imagined interactions (IIs) are discussed. Selected studies in both areas are reviewed. Inner speech originally was conceptualized as a stage in language acquisition and the process of thought. It reflects speaking to oneself in the form of monologue. It has been referred to as verbal thinking, inner speaking, covert self-talk, internal monologue, and internal dialogue as people talk to themselves in silence. IIs are similar, yet different in that imaginary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Arvidsson (2006) expounds on the capability of imagination in digital dating, "It is suggested that such 'fantasy work'the work of imagining situations, people, and relationsis activated to an unprecedented extent in the online economy…Dating sites are where the powers of fantasy are stimulated " (p. 672, 678). Imagined interactions (IIs) have similarly been used to describe this type of fantasy/imagination work involved in interpersonal relationships (Honeycutt, 2003(Honeycutt, , 2010(Honeycutt, , 2020LeFebvre et al, 2021;Vickery, 2019) and have a clear use in CMC and digital dating. The present study seeks to apply the interpersonal construct of IIs to CMC, specifically in the realm of online dating, to explore the nature of imagination work while using dating apps and sites.…”
Section: Introductionmentioning
confidence: 99%
“…Arvidsson (2006) expounds on the capability of imagination in digital dating, "It is suggested that such 'fantasy work'the work of imagining situations, people, and relationsis activated to an unprecedented extent in the online economy…Dating sites are where the powers of fantasy are stimulated " (p. 672, 678). Imagined interactions (IIs) have similarly been used to describe this type of fantasy/imagination work involved in interpersonal relationships (Honeycutt, 2003(Honeycutt, , 2010(Honeycutt, , 2020LeFebvre et al, 2021;Vickery, 2019) and have a clear use in CMC and digital dating. The present study seeks to apply the interpersonal construct of IIs to CMC, specifically in the realm of online dating, to explore the nature of imagination work while using dating apps and sites.…”
Section: Introductionmentioning
confidence: 99%
“…The function of an II is essentially its use, or why a person is experiencing an II-how it is functioning for that individual. Among the functions that have been identified by researchers are catharsis, relational maintenance, rehearsal, conflict linkage, compensation, and self-understanding (Honeycutt, 2003b(Honeycutt, , 2008(Honeycutt, , 2020. To better understand these functions, they can be broken down based on when and why they are experienced.…”
Section: Imagined Interaction Theorymentioning
confidence: 99%
“…Relational maintenance, as a function of IIs, allows one to prepare for or reflect on conversations had with close friends, relatives, or colleagues and is important for relationships that stretch over time and space; as people are currently separated from loved ones, friends, and close colleagues, how individuals experience IIs that fulfill the relational maintenance function will, theoretically, have changed as many relationships have had to move online (Honeycutt, 2009). The rehearsal function of IIs allows a person to plan ahead for potential communication episodes and has been proven to reduce public speaking anxiety (Honeycutt et al, 2009;Honeycutt, 2020) and improve performance (Choi et al, 2015;Gotcher & Honeycutt, 1989;May & Asken, 1987). As boardroom presentations, education, and much more has shifted online, it would seem that the rehearsal function of IIs would continue to function in a similar manner, as individuals prepare for virtual communication.…”
Section: Imagined Interaction Theorymentioning
confidence: 99%
See 2 more Smart Citations